Aramid-HDPE Composites: Influence of Interface Adhesion Measured by T-peel Test on Tensile Properties - Bekem, Aylin; Dogu, Mustafa; Gemici, Zafer; Unal, Ahmet; Guler, Mehmet Hilmi (CARL HANSER VERLAG, 2014)
In this study, the influence of using compatibilizer as tie-layer between fiber matrix interfaces in continuous aramid fiber reinforced high density polyethylene (HDPE) composites was investigated. Maleic anhydride (MAH) grafted polyethylene and ethylene-methyl acrylate-glycidyl methacrylate (EMA-GMA) terpolymer were used as compatibilizers at varying layer numbers. Adhesion strength was determined by T-peel test, and tensile test was carried out. It was found that higher MFR (Melt Flow Rate) valued matrix and compatibilizer application increased the mechanical performance. The maximum strength values were obtained with EMA-GMA applications. In observations of peeled parts and cross-sectional slices, interface adhesion was investigated and failure patterns were determined. It was seen that the samples with compatibilizer had more wetted portions especially the EMA-GMA tie-layered ones.
Keywords: Adhesion; aramid fiber; HDPE; interface; mechanical properties; MECHANICAL-PROPERTIES; FIBER; Materials Science